Asian and Pacific American education : learning, socialization, and identity - Park, Clara C., 1944-; Endo, Russell; Goodwin, A. Lin (Research on the education of Asian and Pacific Americans., 2006)
This research anthology is the third volume in a series sponsored by the Special Interest Group -Research on the Education of Asian and Pacific Americans (SIG-REAPA) of the American Educational Research Association and National Association for Asian and Pacific American Education. This series explores and explains the lived experiences of Asian and Pacific Americans as they attend schools, build communities and claim their place in U.S. society, and blends the work of well-established Asian American scholars with the voices of emerging researchers and examines in close detail important issues in the Asian/Pacific American community. Scholars and educational practitioners will find this book to be an invaluable and enlightening resource.